Baroreflex Sensitivity Predicts Response to Metoprolol in Children With Vasovagal Syncope: A Pilot Study - Chunyan Tao; Chunyan Tao; Xueying Li; Chaoshu Tang; Chaoshu Tang; Hongfang Jin; Hongfang Jin; Junbao Du; Junbao Du (Frontiers in Neuroscience, 2019)
Objective: To explore the role of baroreflex sensitivity (BRS) in the head-up tilt test (HUTT) in predicting the therapeutic response of vasovagal syncope (VVS) patients to metoprolol.Materials and Methods: Vasovagal syncope patients treated with metoprolol were enrolled in this study and were classified as responders or non-responders according to changes in their symptom scores before and after metoprolol treatment. Values of BRS in the supine position and at positive response occurrence in the HUTT were obtained, and BRS changes from supine to positive response occurrence were calculated. Differences between responders and non-responders were analyzed. Receiver operating characteristic curve analysis was performed to assess the value of BRS for predicting the therapeutic efficacy of metoprolol in pediatric patients with VVS.Results: Forty patients (14 boys; 11.8 ± 2.5 years) diagnosed with VVS were recruited in the study, 28 of whom were verified to be responders to metoprolol and 12 of whom were verified as non-responders. They did not show any differences in baseline characteristics and hemodynamics in the HUTT (p > 0.05). However, the responders had an obviously increased supine BRS value compared to the non-responders (16.9 ± 7.7 ms/mmHg vs. 7.6 ± 3.8 ms/mmHg; p < 0.01). No difference in BRS at positive response occurrence was observed between the two groups (8.9 ± 8.5 ms/mmHg vs. 10.6 ± 9.8 ms/mmHg; p > 0.05). Accordingly, the changes in the BRS of responders were more obvious than in non-responders (8.0 ± 7.8 ms/mmHg vs. −3.0 ± 10.4 ms/mmHg; p < 0.01). The area under the receiver operating characteristic curve for the predictive value of supine BRS was 0.887 (95% CI, 0.779–0.995; p < 0.01). A cut-off value of 10 ms/mmHg yielded a sensitivity and specificity of 82 and 83%, respectively, in predicting the therapeutic efficacy of metoprolol in pediatric VVS patients. The area under the receiver operating characteristic curve for the predictive value of BRS changes was 0.827 (95% CI, 0.693–0.962; p < 0.01). A cut-off value of 4 ms/mmHg yielded a sensitivity and specificity of 71 and 83%, respectively.Conclusion: Baroreflex sensitivity may predict the response of children with VVS to metoprolol.